2018
DOI: 10.1016/j.xphs.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Effects on Lipid-Based Vesicles Properties

Abstract: Understanding the effect of surfactant properties is critical when designing vesicular delivery systems. This review evaluates previous studies to explain the influence of surfactant properties on the behavior of lipid vesicular systems, specifically their size, charge, stability, entrapment efficiency, pharmacokinetics, and pharmacodynamics. Generally, the size of vesicles decreases by increasing the surfactant concentration, carbon chain length, the hydrophilicity of the surfactant head group, and the hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
142
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 202 publications
(154 citation statements)
references
References 99 publications
(136 reference statements)
7
142
0
5
Order By: Relevance
“…For compound 1 A , DLS results depended on concentration: it was impossible to obtain good correlograms below the cac, whereas particles with variable, concentration‐dependent sizes in a range from 97.4±42.5 nm (at 500 μ m ) to 244.7±147.3 nm (at 120 μ m ) and good polydispersity values (PDI ≈0.17 and 0.27, respectively) were observed over that threshold (Figure A). This inverse relationship between size and polydispersity values with concentration is common for vesicles from both ionic and neutral surfactants and, together with the found size range and microscopy observations described below, suggests the possible vesicular nature of the 1 A assemblies. Compound 1 T , in contrast, showed narrow signals in the same size range (Figure B); that is, from 86.0±35.2 nm (at 500 μ m ) to 148.8±63.9 nm (at 10 μ m ), with low polydispersity values (PDI ≈0.16 and 0.18, respectively) for the whole range of concentrations at which this dinucleolipid self‐assembles (from 10 μ m 1 T ).…”
Section: Resultsmentioning
confidence: 99%
“…For compound 1 A , DLS results depended on concentration: it was impossible to obtain good correlograms below the cac, whereas particles with variable, concentration‐dependent sizes in a range from 97.4±42.5 nm (at 500 μ m ) to 244.7±147.3 nm (at 120 μ m ) and good polydispersity values (PDI ≈0.17 and 0.27, respectively) were observed over that threshold (Figure A). This inverse relationship between size and polydispersity values with concentration is common for vesicles from both ionic and neutral surfactants and, together with the found size range and microscopy observations described below, suggests the possible vesicular nature of the 1 A assemblies. Compound 1 T , in contrast, showed narrow signals in the same size range (Figure B); that is, from 86.0±35.2 nm (at 500 μ m ) to 148.8±63.9 nm (at 10 μ m ), with low polydispersity values (PDI ≈0.16 and 0.18, respectively) for the whole range of concentrations at which this dinucleolipid self‐assembles (from 10 μ m 1 T ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, natural and synthetic phospholipids (EPC and DMPC) were investigated in this study. Additionally, it was reported that the surfactant type and concentration can also affect transfersome size and %EE . For this reason, three surfactants (EA) were used in this DOE in three different percentages (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was reported that the surfactant type and concentration can also affect transfersome size and % EE. [18] For this reason, three surfactants (EA) were used in this DOE in three different percentages ( Table 2). Lidocaine-loaded transfersomes were prepared according to the designed experiments (Table 3).…”
Section: Transfersome Optimisation and Taguchi Doe Analysismentioning
confidence: 99%
See 2 more Smart Citations